2004
DOI: 10.1677/joe.0.1800175
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of insulin-like growth factor I prevents streptozotocin-induced cardiac contractile dysfunction and beta-adrenergic response in ventricular myocytes

Abstract: Diabetic cardiomyopathy is characterized by cardiac dysfunction and altered level/function of insulin-like growth factor I (IGF-I). Both endogenous and exogenous IGF-I have been shown to effectively alleviate diabetes-induced cardiac dysfunction and oxidative stress. This study was designed to examine the effect of cardiac overexpression of IGF-I on streptozotocin (STZ)-induced cardiac contractile dysfunction in mouse myocytes. Both IGF-I heterozygous transgenic mice and their wild-type FVB littermates were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
38
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 35 publications
11
38
0
Order By: Relevance
“…These data are consistent with our previous findings from both chemically induced and genetically predisposed rodent diabetic models (11,21,22,24,26,33). UCF-101 itself failed to alter these mechanical properties in the absence of diabetes, whereas it restored almost all STZ-induced mechanical defects with the exception of peak shortening.…”
Section: Discussionsupporting
confidence: 92%
“…These data are consistent with our previous findings from both chemically induced and genetically predisposed rodent diabetic models (11,21,22,24,26,33). UCF-101 itself failed to alter these mechanical properties in the absence of diabetes, whereas it restored almost all STZ-induced mechanical defects with the exception of peak shortening.…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that hearts from diabetic rats showed significantly reduced contractility and prolonged diastole in vivo, which are hallmarks of diabetic cardiomyopathy. These findings are in agreement with other studies [26][27][28] . Consistent with their impaired cardiac function, diabetic rats developed myocardial fibrosis, the marked fibrotic regions (as observed by immunohistochemical staining), as well as deposition of collagen fibers in the interstitial spaces among cardiomyocytes (as observed by TEM), our observations are similar to those described in other reports [29,30] .…”
Section: Discussionsupporting
confidence: 94%
“…IGF-1 may also elicit cardiac protection against diabetes involving attenuated p53 function, angiotensin II production and angiotensin receptor activation . Our studies suggested that IGF-1 may rescue the diabetes-induced reduction in SERCA protein abundance and impaired -adrenergic responsiveness (Norby et al 2002(Norby et al , 2004. In addition, diabetic tissues including hearts usually display IGF-1 resistance (Rodgers et al 1995, Kelley et al 1999, Ren et al 1999a, Ren 2000, making glucose clearing by IGF-1 largely dependent on crossreaction with the insulin receptor, which requires higher levels of IGF-1 agonist.…”
Section: Discussionmentioning
confidence: 79%